Optical Temperature Sensing With Infrared Excited Upconversion Nanoparticles - Green, Kory; Huang, Kai; Pan, Hai; Han, Gang; Lim, Shuang Fang (Frontiers in Chemistry, 2018)
Upconversion Nanoparticles (UCNPs) enable direct measurement of the local temperature with high temporal and thermal resolution and sensitivity. Current studies focusing on small animals and cellular systems, based on continuous wave (CW) infrared excitation sources, typically lead to localized thermal heating. However, the effects of upconversion bioimaging at the molecular scale, where higher infrared intensities under a tightly focused excitation beam, coupled with pulsed excitation to provide higher peak powers, is not well understood. We report on the feasibility of 800 nm and 980 nm excited UCNPs in thermal sensing under pulsed excitation. The UCNPs report temperature ratiometrically with sensitivities in the 1x10-4 K-1 range under both excitation wavelengths. Our optical measurements show a ln(I525/I545) versus 1/T dependence for both 800 nm and 980 nm excitations. Despite widespread evidence promoting the benefits of 800 nm over 980 nm CW excitation in avoiding thermal heating in biological imaging, in contrary, we find that given the pulsed laser intensities appropriate for single particle imaging, at both 800 nm and 980 nm, that there is no significant local heating in air and in water. Finally, in order to confirm the applicability of infrared imaging at excitation intensities compatible with single nanoparticle tracking, DNA tightropes were exposed to pulsed infrared excitations at 800 nm and 980 nm. Our results show no appreciable change in the viability of DNA over time when exposed to either wavelengths. Our studies pave the way for exploring protein-DNA interactions at the single molecule scale, using UCNPs as a reporter.